Spatiotemporal dynamics and predictive modelling of land use and land cover changes for sustainable watershed management in the Karamana River Basin, India - Ganga Krishnan; Radhakrishnan Shanthi Priya; Geetha Ramesh Kumar; Ramalingam Senthil (Results in Engineering)
The Karamana River basin in Kerala, India, has undergone significant changes in land use and land cover (LULC) over 40 years. This study examines the spatiotemporal dynamics of LULC changes from 1985 to 2024 and projects a future scenario for the year 2050 using the Cellular Automata–Markov (CA–Markov) chain modeling approach. Multi-temporal satellite imagery was analyzed to classify LULC into nine categories, followed by change detection analysis and spectral indices to quantify the nature and extent of transformation. Between 1985 and 2024, built-up areas increased by approximately 219 %, while evergreen forests decreased by 38 %. An analysis of the normalized difference vegetation index indicated a decline in dense vegetation from 75 % in 1985 to 20 % in 2024, reflecting a progressive reduction in vegetation density. Conversely, normalized difference built-up index values rose from 5 % to 40 %, signifying an increase in urban density. The CA–Markov model forecasts further expansion of built-up land from 110.8 km² in 2024 to 430 km² in 2050. The projection map suggests that the primary LULC classes will be built-up and mixed vegetation. The LULC classification accuracy was estimated to have an average Kappa coefficient of 0.81 and an overall accuracy of 81.31 %. The assessed trends highlight the increasing pressure on the basin’s ecological resources from unregulated urban development. The findings provide crucial insights into the past, present, and projected future, offering valuable guidance for policymakers and planners focused on sustainable urban and watershed management in alignment with Sustainable Development Goals 6, 11, 12 and 15.